Are financial markets embedded in economics rather than society? A critical review of the performativity thesis - Lasse Folke Henriksen (Danish Institute for International Studies (DIIS), 2009)
DIIS Working Paper reviews a recent influential branch within the Social Studies of Finance literature which asserts that financial markets are embedded in economics rather than in soci-ety (as scholars of the New Economic Sociology would have it). Coming from actor-network theory, the literature contributes conceptually to an extended ontology of markets and agency and empirically to an improved understanding of the importance of economist's role in con-structing markets and assembling economic agency. It also draws attention to the staggering effects that material devices and technical 'details' can potentially have on the macrodynamics of financial markets. In some cases financial markets can even be performed by economics, that is, materialized in very close accordance with the economic models that describe them. From this insight they conclude that economics is a performative science and that the social sciences should consequently break down the Great (analytical) Divide between finance the-ory and financial markets. However, the review finds that the literature is marked by a methodological bias. The lit-erature works with the microsociological methods of actor-network theory and thus tends to deliver pragmatically adequate explanations of the unique local social orders observable in 'the financial laboratory'. This means that it has its primary focus on the mutual entangle-ments of 'universities' and 'markets', that its preferred protagonist's are the economist's and that its privileged object of analysis is economic technology. Its pragmatic outlook also gives it a preference for 'market success' rather than failure and it often exaggerates the capacity of economist's to perform markets. It tends to forget the role of politicians, political technolo-gies, macro actors such as the state and international organizations not to mention the global asymmetries connected with the political economy of financialized capitalism. Although the performativity tradition must be seen as a further analytical development of Foucaults knowl-edge-power nexus, in particular his concept of 'dispositif', its focus on studying the 'labora-tory' (situated social practices) disregards the historical paradigmatic forms of the 'archive' which also condition financial agency. A fruitful dialogue between the pragmatism of perfor-mativism and a historically oriented poststructuralism inspired by Foucaults dispositif analysis is called for in the future course of Social Studies of Finance.
Keywords: 330; Finanzmarkt; Marktmechanismus; Wirtschaftssoziologie; Theorie